Nexuses between knowledge and policy: China studies in Pakistani think tanks - Mahesar, Pervaiz Ali; Ngeow, Chow Bing; Rogers, Roy Anthony (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2019)
This article looks at China studies produced in Pakistani think tanks, and then it explores nexuses between knowledge and policy. Think tanks are considered as ‘knowledge reservoirs’. Their knowledge is taken as input and feedback on important policy issues. Their close relationship with policy institutions, in terms of, their contributions, feedback, inputs, and ideas help shape policies. In Pakistan, think tanks have played a pivotal role in generating ideas, discourses and public opinion in society. Interestingly, these domestic images on China and Pakistan-China relations in Pakistani think tanks show how historical knowledge could contribute to shaping Pakistan’s China policy. The study argues that the previous studies on China and Pakistan-China relations have been dictated by power politics factors in which India and US have loomed large. In this article, a Constructivist perspective of International Relations is chosen to understand, how ideas, discourses, studies, and knowledge could shape Pakistan’s policy towards China. Adopting the qualitative approach, this research collected data through primary and secondary sources. It conducted interviews from the senior think tank analysts in Pakistan. This study revealed that indigenous knowledge produced in Pakistani think tanks, in particular, China Studies, have positively contributed to shaping Pakistan’s China policy.